Development of dual-targeted nano-dandelion based on an oligomeric hyaluronic acid polymer targeting tumor-associated macrophages for combination therapy of non-small cell lung cancer. (1st January 2019) - Wang, Bingjie; Zhang, Wei; Zhou, Xiudi; Liu, Mengna; Hou, Xiaoya; Cheng, Ziting; Chen, Daquan
Abstract: In this study, the novel carrier materials were screened to structure targeting nano-micelles (named 'nano-dandelion') for synchronous delivery of curcumin (Cur) and baicalin (Bai), which could effectively overcome the tumor resistance. Mannose (Man) was found to bind better to CD206 receptors on the surface of tumor-associated macrophages (TAMs), thereby increasing the number of nano-dandelion engulfed by TAMs. Furthermore, oligomeric hyaluronic acid (oHA) was able to target CD44 receptors, resulting in recruitment of a higher number of nano-dandelion to locate and engulf tumor cells. The disulfide bond (S–S) in 3, 3′-dithiodipropionic acid (DA) could be broken by the high concentration of glutathione (GSH) in the tumor microenvironment (TME). Based on this, we selected DA to connect hydrophobic fragments (quercetin, Que) and oHA. A reduction-sensitive amphiphilic carrier material, quercetin–dithiodipropionic acid–oligomeric hyaluronic acid–mannose–ferulic acid (Que–S–S–oHA–Man–FA; QHMF) was fabricated and synthesized by 1 H NMR. Next, QHMF self-assembled into nano-dandelion, i.e. encapsulated Cur and Bai in water. Critical experimental conditions in the preparation process of nano-dandelion that could affect its final properties were explored. Nano-dandelion with a small particle size (121.0 ± 15 nm) and good normal distribution (PI = 0.129) could easily enter tumor tissue through vascular barrier. In addition, nano-dandelion with a suitable surface potential (–20.33 ± 4.02 mV) could remain stable for a long duration. Furthermore, good cellular penetration and tumor cytotoxicity of nano-dandelion were demonstrated through in vitro cellular studies. Finally, effective antitumor activity and reduced side effects were confirmed through in vivo antitumor experiments in A549 tumor-bearing nude mice.